Friendship Quality and Gender Differences in Association With Cyberbullying Involvement and Psychological Well-Being - Foody, Mairéad; McGuire, Lian; Kuldas, Seffetullah; O’Higgins Norman, James (Frontiers in Psychology, 2019)
Current literature has documented the detrimental effects of cyberbullying which include a range of internalising and externalising problems for those involved. Although critical, this research can sometimes ignore social-ecological aspects of a child’s life that can potentially ‘buffer’ the negative psychological effects of such involvement. With this in mind, this cross-sectional investigation of 12-16 year olds [M(SD): 13.5(1) years] in Ireland focused on the role of friendship quality and gender in association with cyberbullying involvement and psychological well-being (N= 2410). The Cyberbullying and Online Aggression Scale was used to measure cyber perpetration and victimisation. A modified version of the Cambridge Friendship Questionnaire was included to investigate peer friendship quality. Finally, the Moods and Feeling Questionnaire and the Strengths and Difficulties Questionnaire were chosen to provide a measurement of psychological well-being. Prevalence rates for various types of cyberbullying roles (cyber bullies, victims and bully/victims) are presented, as well as differences for psychological well-being, friendship quality and cyberbullying involvement. In addition, regression models were used to determine the associations between gender, age, friendship quality and involvement in cyberbullying with psychological well-being. The results are considered in terms of the current literature and directions for future research are suggested.